Do Professional Teachers Not Experience Stress? How does Islamic Perspective Manage Stress? - Anis Fauzi; Imroatun Imroatun; Ayu Jumaela; Yuli Rohmiyati; Anas Nasrudin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2022)
This article aims to show how to manage stress in forming a professional teacher. The research method used is descriptive qualitative with the type of library research. The data analysis technique used is a content analysis pattern. This study explains that managing stress is to maintaining relations with fellow human beings based on an Islamic perspective. The conclusions are: First, how to manage stress according to the existing situation, namely: Faith in Allah SWT, sincere intention to practice the knowledge possessed by students, Absorbing the meaning of prayer and dhikr that we always pray to Allah SWT, Put your trust in Allah SWT, Accept what is the current situation and conditions, Be patient in dealing with all problems, and Always be grateful for the blessings that Allah SWT has given. Second, because life is a reality that must be experienced, every human being, must experience symptoms of stress in their lives.